2007
DOI: 10.1093/jxb/erm271
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specialization at the metabolite level is perceived during the development of tomato fruit

Abstract: Fruit maturation and tissue differentiation are important topics in plant physiology. These biological phenomena are accompanied by specific alterations in the biological system, such as differences in the type and concentration of metabolites. The secondary metabolism of tomato (Solanum lycopersicum) fruit was monitored by using liquid chromatography (LC) coupled to photo-diode array (PDA) detection, fluorescence detection (FD), and mass spectrometry (MS). Through this integrated approach different classes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
179
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(198 citation statements)
references
References 47 publications
17
179
1
1
Order By: Relevance
“…2-4), in accordance with the different cell size and shape in these tissues (Fig. 1) and with published results (Moco et al, 2007). Organic acids (malate, citrate, and fumarate) as well as GABA, acidic amino acids (Glu and Asp), and some soluble sugars (Suc and UDP-Glc) were more abundant in locular tissue at the end of the cell expansion period.…”
Section: Discussionsupporting
confidence: 90%
“…2-4), in accordance with the different cell size and shape in these tissues (Fig. 1) and with published results (Moco et al, 2007). Organic acids (malate, citrate, and fumarate) as well as GABA, acidic amino acids (Glu and Asp), and some soluble sugars (Suc and UDP-Glc) were more abundant in locular tissue at the end of the cell expansion period.…”
Section: Discussionsupporting
confidence: 90%
“…A possible explanation for this disparity is that gene expression is not uniform across the different fruit tissues during ripening. This hypothesis is supported by a study of tissue-specific metabolites during tomato development, where differences in metabolite profiles were detected between specific tissues and at different ripening stages (Moco et al, 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Information theory has been used for multivariate data generated in a broad scope of biological contexts ranging from plant ecology (23) to microbiome diversity (24), but, to our knowledge, it has never been used to summarize trends in MS-based metabolomics data. Previous studies identified preferential tissue-based redirectionalities in secondary metabolism, for instance, during the maturation of tomato fruits for which the green, turning, and red developmental stages are characterized by rearrangements in pathways related to flavonoids, phenolics, and glycoalkaloids (25). However, to our knowledge, no unbiased metabolomics study, other than a study of the AtMetExpress database (6), has been applied with rigorous statistical analysis to such a broad range of tissues as in the present study.…”
Section: Discussionmentioning
confidence: 93%